Trust in science and in government plays a crucial role in COVID-19 response - Resnick, Danielle (International Food Policy Research Institute, 2022)
In April 2020, Tanzania’s prime minister made a simple plea: “Tanzanians should maintain trust in the government. You should continue to trust our experts who are behind every decision we make.” A month later, the country’s then president, John Magufuli, fired the head of its national COVID-19 test laboratory and committed to importing an untested herbal tonic from Madagascar that was controversially touted as a cure for the novel coronavirus despite scientists’ worries that it could lead to drug-resistant malaria.